First year undergraduates make use of recordings to overcome the barriers to higher education: evidence from a survey - Jill R.D. MacKay (Association for Learning Technology, 2020)
In this study, 295 (13.8% response rate) first year students from a large, Scottish, Russell-Group university were surveyed on their attitudes to and use of lecture recordings in 2018. Kruskal-Wallis tests were used to compare the ranked responses between students in different categories relevant to monitoring equality and diversity, such as carer status (5% of respondents), learning adjustments (9% of respondents) and non-native English speakers (27% of respondents). Students most commonly watched a full lecture by themselves when studying with 60% watching a full lecture at least once a week. Non-native English speakers were more likely to watch specific parts of a lecture more frequently (H2 = 8.52, p = 0.014). Students with learning adjustments more often reported being unable to find a resource (H3 = 8.356, p = 0.039). There was no effect of students' language, carer status or learning adjustment status on their self-reported likelihood to attend a lecture, likelihood to change note-taking behaviour or concentrate on a lecture if it was being recorded. Non-native English speakers were still more likely to worry about keeping up with a lecture, even when it was being recorded (H2 = 10.492, p = 0.005). In conclusion, lecture recording has different impacts on students from different backgrounds, and inclusive lecture recording education policies need to consider this impact.